Geographic Information System (GIS) of student and scholarship distribution in Jambi Province using QGIS - Rachmawati, Aulia; Alghifari, Hamzah; anzari, Yandi; Yulvianda, Renaldi (Journal of Computer-based Instructional Media, 2025)
Education is one of the main pillars in developing quality human resources. To ensure equal access to education, the government has launched various scholarship programs. However, the management and distribution of scholarships often face challenges in terms of accurate data collection and spatial distribution analysis. This study aims to map the distribution of scholarship recipients in Jambi Province using a Geographic Information System (GIS) approach with QGIS software. The research uses spatial data in the form of administrative boundaries of Jambi Province and non-spatial data on the number of scholarship recipients per district/city obtained from the JDAC Jambi official website. The data were processed using attribute joining, classification with the Natural Breaks (Jenks) method, and visualization through a choropleth map. The results show that scholarship recipients are unevenly distributed, with higher concentrations in urban and densely populated areas such as Jambi City and Muaro Jambi Regency, while regions like Tebo and Sarolangun have relatively low numbers. This indicates the influence of population density, availability of higher education institutions, and information accessibility on scholarship distribution. The use of QGIS proved effective in presenting spatial data visually and supporting data-driven policymaking. The study recommends that local governments utilize spatial analysis in scholarship distribution planning to enhance equity and program effectiveness.